2020
DOI: 10.30539/ijvm.v44i(e0).1015
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Infectious Bursal Disease Virus Isolated from Naturally Infected Broiler Chickens in Erbil, Iraq

Abstract: The infectious bursal disease (IBD) is a highly contagious and immunosuppressive disease of broiler chickens and the development of a new genetic variant of the virus is responsible for major economic losses in the poultry industry. For this purpose, it was essential to isolate the molecular characterization of the virus from vaccinated broiler in Erbil, Iraq. Clinically, the infectious bursal disease is characterized by high mortality (10-15%) with hemorrhagic lesions on the breast and thigh muscles, hemorrha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
(29 reference statements)
1
0
0
Order By: Relevance
“…HI and AGID tests utilizing NDV-specific hyperimmune serum revealed that all 60 isolates tested positive for NDV. The HI test results of the current study support the findings of Ahmed and Odisho [ 31 ], El-Bagoury et al [ 32 ], and Seal et al [ 33 ], who confirmed NDV by the HI test. Hasan et al [ 25 ] and Mohammed et al [ 34 ] detected the NDV virus in field samples utilizing hyper-immune serum of NDV by AGID test.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…HI and AGID tests utilizing NDV-specific hyperimmune serum revealed that all 60 isolates tested positive for NDV. The HI test results of the current study support the findings of Ahmed and Odisho [ 31 ], El-Bagoury et al [ 32 ], and Seal et al [ 33 ], who confirmed NDV by the HI test. Hasan et al [ 25 ] and Mohammed et al [ 34 ] detected the NDV virus in field samples utilizing hyper-immune serum of NDV by AGID test.…”
Section: Discussionsupporting
confidence: 91%
“…The ICPI, IVPI, and MDT assays confirmed that the isolates were velogenic strains of NDV, which is similar to the findings of Rashi et al [ 41 ], Ahmed and Odisho [ 31 ], and Kommers et al [ 42 ]. The MDT in chicken embryos and the ICPI in day-old chicks were two of the pathogenicity tests carried out by Nooruzzaman et al [ 7 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The study also showed that the prevalence of infection was significantly higher in backyard chickens than in commercial chickens [20]. Similarly, a separate study conducted in the Kurdistan region of (northern Iraq) showed a lower infection rate than the present study [21]. Numerous factors, such as the geographical region and the specific breed of birds, might influence the distribution of NDVs.…”
Section: Discussionsupporting
confidence: 56%